Synthetic Cystic Fibrosis Sputum Medium Regulates Flagellar Biosynthesis through the flhF Gene in Burkholderia cenocepacia - Kumar, Brijesh; Cardona, Silvia T. (Frontiers in Cellular and Infection Microbiology, 2016)
Burkholderia cenocepacia belongs to the Burkholderia cepacia complex (Bcc), a group of at least 18 distinct species that establish chronic infections in the lung of people with the genetic disease cystic fibrosis (CF). The sputum of CF patients is rich in amino acids and was previously shown to increase flagellar gene expression in B. cenocepacia. We examined flagellin expression and flagellar morphology of B. cenocepacia grown in synthetic cystic fibrosis sputum medium (SCFM) compared to minimal medium. We found that CF nutritional conditions induce increased motility and flagellin expression. Individual amino acids added at the same concentrations as found in SCFM also increased motility but not flagellin expression, suggesting a chemotactic effect of amino acids. Electron microscopy and flagella staining demonstrated that the increase in flagellin corresponds to a change in the number of flagella per cell. In minimal medium, the ratio of multiple: single: aflagellated cells was 2:3.5:4.5; while under SCFM conditions, the ratio was 7:2:1. We created a deletion mutant, ∆flhF, to study whether this putative GTPase regulates the flagellation pattern of B. cenocepacia K56-2 during growth in CF conditions. The ∆flhF mutant exhibited 80% aflagellated, 14% single and 6% multiple flagellated bacterial subpopulations. Moreover, the ratio of multiple to single flagella in WT and ∆flhF was 3.5 and 0.43, respectively in CF conditions. The observed differences suggest that FlhF positively regulates flagellin expression and the flagellation pattern in B. cenocepacia K56-2 during CF nutritional conditions.